Muscle Activity and Posture Differences in the Sit and Stand Phases of Sit-to-Stand Workstation Use: A Comparison of Computer Configurations. Issue 4 (1st October 2016) - Babski-Reeves, Kari; Calhoun, Alex
Abstract : OCCUPATIONAL APPLICATIONS We found differences in muscle activity, joint angles, and discomfort ratings between seated versus standing computerized work, with the standing phase resulting in "better" measures. Given that sit-to-stand workstations are gaining popularity, identifying such differences can help minimize exposure to ergonomic risks during computing tasks—particularly during the standing phase of the work task. For example, workers positioned themselves closer to the work station while standing, which resulted in reduced muscular loads and more neutral joint angles. By adjusting seated postures to more closely reflect standing postures, low level muscle fatigue and discomfort can be minimized. TECHNICAL ABSTRACT Background : Prolonged seated work has been associated with a number of adverse health conditions, and the use of sit-to-stand workstations have been shown to provide benefits for those employed in primarily sedentary work tasks, such as computer tasks. However, little research has been reported on potential differences in musculoskeletal loading and postures during the sit versus stand phases of data entry tasks. Purpose : The purpose of this study was to quantify differences in muscle activity level, joint angle, discomfort in the trunk and upper extremity, and body positioning relative to the workstation while using a sit-to-stand workstation for a simulated data entry task. Methods : A repeated measures design was used to study the effects of computer configuration (desktop, docked laptop with peripherals, and laptop) and sit/stand phase (seated or standing) on muscle activity, posture, and reports of discomfort. Twenty-four participants (12 males and 12 females) completed three cycles of a 20/5 sit-to-stand ratio (20 minutes seated, 5 minutes standing) during a data entry task. Surface electromyography of the shoulders, forearm, and lower back were used to estimate muscle activity levels; electrogoniometers were used to track elbow, neck, and back angles, and discomfort was measured using a body discomfort map. Repeated measures analysis of variance and Tukey's honest significant difference post hoc tests were used to determine statistical differences between conditions. Results : Computer configuration, in general, was not found to significantly affect the dependent measures, though the sit/stand phase did. The seated phase resulted in more non-neutral working postures than standing, which were likely associated with body positioning relative to the workstation and computer. Participants positioned themselves further from the computer and workstation while seated than while standing. Seated work resulted in higher upper trapezius activity than when standing (4.9% versus 2.4%). Conclusions : While sit-to-stand workstations may present long term health benefits, there are likely tradeoffs for the musculoskeletal system—particularly during the seated phase of the work. Workers may benefit from training on body positioning during both phases to ensure neither phase of the work increases musculoskeletal risks.